1951
DOI: 10.1085/jgp.34.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Culture Media

Abstract: 1. Human placental cord serum contains a factor or factors necessary for active growth of fibroblasts in tissue culture and a factor which prevents the appearance of a characteristic toxicity. 2. The growth-promoting factor(s) is stable to heating to 60°C. for 30 minutes and is associated with the euglobulin fraction of the serum. 3. Extraction of dried cord serum with benzene, chloroform, and ether does not cause any decrease in growth-promoting activity. 4. Sera f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1952
1952
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This possibility is suggested by results obtained with the twenty initial run curtain fractions (Table III, part B); growth enhancement and nucleolar reactivity were not always present together. However, in the early studies of Jacquez and Barry (17), growthsupporting properties were found in the euglobulins and albumins; as mentioned above, alpha and beta globulins and albumins have held the center of interest as serum growth promoting fractions (15). The few fractions of serum possessing both nucleolar reactivity and growth promotion thus present a problem of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is suggested by results obtained with the twenty initial run curtain fractions (Table III, part B); growth enhancement and nucleolar reactivity were not always present together. However, in the early studies of Jacquez and Barry (17), growthsupporting properties were found in the euglobulins and albumins; as mentioned above, alpha and beta globulins and albumins have held the center of interest as serum growth promoting fractions (15). The few fractions of serum possessing both nucleolar reactivity and growth promotion thus present a problem of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…COHN, E. J., STRONG, L. E., HUGHES, W. L., where serum proteins are required, their manner of promoting growth remains unknown at the molecular level (15,17,18,19). The two lines of reasoning might converge in a new concept for the study of the nucleolar role in ribosome formation (20).…”
mentioning
confidence: 99%
“…Whether one, a few, or all of these components are uniquely or alter-natively requisite for the albumin contribution to $3 growth here described remains to be determined. Nor is anything known of the nature of the albumin function--whether it be to serve as an essential nutrilite itself; to provide a dissociable component, or a frank impurity, undetectable by the methods so far employed, which constitutes the actual active substance; to assist in transport of some other molecule; to regulate metabolic balance; or to detoxify media (14) containing injurious levels of certain constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Harris (20) concluded that the defined media then existing were all deficient in one or more factors that occur in serum dialysate and are essential for growth; and, Eagle (11) found that serum does, in fact, contain one or more low molecular weight growth factors, either bound to serum protein or formed from it on proteolysis. In 1951, Jacquez and Barry (25), working with rat cells in washed plasma clots, found that the entire growthpromoting activity of exhaustively dialyzed human placental cord serum was associated with the nondialyzable fraction. More recently, Lockart and Eagle (35) found dialyzed serum as effective as whole serum for heavily seeded cultures but not for cloning experiments with the same cell strains.…”
mentioning
confidence: 99%
“…Fraction G2, which contains macroglobulin and other c~-globulins (4,43), was said to be interchangeable with whole serum for adhesion of cells to glass but not for nutrition. In 1951, Jacquez and Barry (25) prepared albumin and globulin fractions from human placental cord serum by ammonium sulfate precipitation and found all the growth activity of the original serum was present in the globulin fraction. When subfractions were prepared from the globulin fraction, some activity was found in all of them.…”
mentioning
confidence: 99%